ANALISIS HAK KEADILAN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM BAGI MASYARAKAT - Sukamto; Siti Ngainnur Rohmah (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The law enforcement process in Indonesia is still not going well. The problem of law enforcement is still not felt by the lower classes of society. Limited ability both in education, economy and social. even though it is the lower middle class who are very vulnerable to criminal acts. So that this Legal Aid Institute is very much needed by the lower middle class or the poor. The purpose of this study is to determine the implementation of legal aid for the community based on Law No. 16 of 2011 and to determine the granting of justice rights to the community through the Legal Aid Institute. In this study, the author uses a legal research approach that is carried out in a normative juridical manner. normative juridical research is conceptualized as what is written in legislation (law in books) or the law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. The results of the study can be concluded that the implementation of providing legal assistance to the poor in order to seek legal justice has not been implemented properly. Because there is still limited information and education for people who can't afford legal aid.